PENGARUH MOTIVASI, LINGKUNGAN KERJA, KESEJAHTERAAN, DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH MENENGAH PERTAMA - Sumaryanto - (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2012)
ABSTRACT The purpose of this study to analysis the influence of motivation, work environment, welfare and principal leadership teacher performance against SMPN 1 Gondangrejo, Karanganyar. The research sample set by using the census, because the population is less than 100, the sample in this study of 40 people, equal to the number population. The data used are primary data using questionnaires completed by respondents. The analysis tools are Multiple Linear Regression analysis, t test, F test and R2 Test. The analysis showed that the Working Environment variables are the most dominant variable in the performance of teachers. The results of the t test motivation variable indicates no significance effect of motivation on performance, the hypothesis unsubstantiated. Work environment variables indicates a positive work environment variables and significant impact on performance improvement, research hypothesis proved to be true because if it is supported by the data. Welfare variable indicates no effect on the performance of the welfare significance, the hypothesis unsubstantiated. Leadership style variable indicates variable leadership style has positive and significant impact on performance improvement, the hypothesis proved to be true because if it is supported by the data. F-test of independent variables jointly affect the performance. Determinant coefficient explains that the set of variables motivation, work environment, welfare and leadership style in the regression model of this study, the effect contributes to the performance of 72.6%. Keywords: Motivation, Work Environment, Welfare, Performance